Cytokine gene polymorphisms implicated in the pathogenesis of Plasmodium falciparum infection outcome - Segbefia, Selorm Philip; Asandem, Diana Asema; Amoah, Linda Eva; Kusi, Kwadwo Asamoah (Frontiers in Immunology, 2024)
Cytokines play a critical role in the immune mechanisms involved in fighting infections including malaria. Polymorphisms in cytokine genes may affect immune responses during an infection with Plasmodium parasites and immunization outcomes during routine administration of malaria vaccines. These polymorphisms can increase or reduce susceptibility to this deadly infection, and this may affect the physiologically needed balance between anti-inflammatory and pro-inflammatory cytokines. The purpose of this review is to present an overview of the effect of selected cytokine gene polymorphisms on immune responses against malaria.